Contract Cheating ‘Pseudepigraphy’. A Cardinal Sin in Higher Education? A Phenomenological Narrative of Andragogical Experiences, Insights and Reflections - Reuben Agbelengor Glover; Cyril Senyo Kpodo; Selasi Awusi Sosu (E-Journal of Humanities, Arts and Social Sciences)
This interpretive phenomenological analysis (IPA) study is a reflection on valuable insights gained by the authors in supervising graduate students’ theses, dissertations, and project works/reports, active participation in seminars on ethics in higher education and first-hand andragogical teaching experiences in the Ghanaian setting. The study explored contract cheating among graduate students and strategic interventions used by faculty to address it. Using an interpretive phenomenological analysis (IPA) in a qualitative narrative paradigm, the study discussed the critical causal factors, strategic interventions, andragogy, heutagogy, support mechanisms and software employed to mitigate graduate students’ indulgence in contract cheating in their final year thesis, dissertations, and project works/reports. Findings revealed that contract cheating among graduate students is influenced by personal, contextual, cultural, situational, institutional, and technological factors, as well as a misconception of widespread participation in higher education. The study recommends a paradigmatic shift away from the punitive and toward the developmental approach when responding to contract cheating. The study contributes new insights to enrich the ongoing scholarly conversation on contract cheating and interventions in Ghanaian universities.